2003
DOI: 10.1212/01.wnl.0000042477.63516.b2
|View full text |Cite
|
Sign up to set email alerts
|

Acute migraine treatment with droperidol

Abstract: A total of 331 patients were enrolled; 305 were treated. Headache response at 2 hours was better (p < 0.002) in the treatment groups receiving droperidol IM at doses of 2.75 mg (87%), 5.5 mg (81%), and 8.25 mg (85%) compared with placebo (57%). The percent of patients achieving a pain-free response at 2 hours after treatment was significantly greater than placebo for the droperidol 2.75-mg, 5.5-mg, and 8.25-mg dose groups. The frequency of headache recurrence (within 24 hours) for patients initially responding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
85
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(88 citation statements)
references
References 25 publications
2
85
1
Order By: Relevance
“…Three studies reported proportions of patients with subjective headache relief 1 to 3 hours post administration of a butyrophenone compared to placebo or meperidine in the treatment of migraine. [13][14][15] The weighted average rate of subjective headache relief 1 to 3 hours after treatment by a butyrophenone in these three trials was 82.8% (n 5 216).…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Three studies reported proportions of patients with subjective headache relief 1 to 3 hours post administration of a butyrophenone compared to placebo or meperidine in the treatment of migraine. [13][14][15] The weighted average rate of subjective headache relief 1 to 3 hours after treatment by a butyrophenone in these three trials was 82.8% (n 5 216).…”
Section: Resultsmentioning
confidence: 94%
“…Two of these studies compared a butyrophenone to placebo in the treatment of migraine. 13,14 One compared intravenous (IV) haloperidol to placebo, 13 whereas the other compared intramuscular (IM) droperidol to placebo using four different dosage regimens. 14 The remaining four studies compared parenteral droperidol to a comparator drug in the treatment of migraine or benign headache.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple clinical trials have showed superior effect compared to placebo, SC sumatriptan and sodium valproate [54][55][56][57]. Intravenous droperidol [58,59] is effective in status migranosus and more effective than placebo in controlled trials for acute migraine. Multiple studies also support the use of chlorpromazine [60,61], haloperidol [62], and metoclopramide [63,64] with or in conjunction with DHE treatment.…”
mentioning
confidence: 99%